Identification of lactic acid bacteria isolated from developed dried coffee starter culture used as a fermentation agent to produce Robusta civet coffee - MUKHAMMAD FAUZI; ACHMAD SUBAGIO; DIDIK PUDJI RESTANTO; JAY JAYUS (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Fauzi M, Subagio A, Restanto DP, Jayus J. 2023. Identification of lactic acid bacteria isolated from developed dried coffee starter culture used as a fermentation agent to produce Robusta civet coffee. Biodiversitas 24: 3715-3722. Native civet coffee is a popular coffee bean, produced by the processes which undergo spontaneous fermentation in the civet digestive system. Since the native civet coffee has a higher selling value and its production depends on the uncontrolled civet life activities, the effort to produce a similar quality of this coffee product has been made by designing a dried starter culture isolated from civet caecum, and utilizing coffee cherry peels as the potential inducer and rice flour as the matrix for coating and immobilizing the isolates. The proportion of rice and coffee cherry peel flour mixtures was formulated to fabricate the dried starter culture by determining the viability and fermentability of lactic acid bacteria (LAB) survive in the starter culture. Furthermore, the starter culture was analyzed for the number of microflora and identification of LAB, water content, glucose fermentability, total titrated acid production rate, and pH value. The most viable starter cultures were obtained from the formula of 80% rice flour and 20% coffee cherry peel flour exhibiting the number of microflora of 5.6 log MPN/g and fermentation capacity of 245.73 mg glucose/gh. The total titrated acid production rate was 91.07 mg lactic acid/gh, and a pH value of 5.33. The LABs survived in the starter culture were identified as Lacticaseibacillus paracasei. The quality of hot brewed roasted Robusta coffee prepared by fermentation using this dried starter culture was higher than that of unfermented one, as observed from their organoleptic quality. These findings indicate that the LAB isolated from civet caecum is potential to be developed as a dried starter culture in coffee cherry fermentation processes.